Pengaruh Biaya Produksi dan Biaya Operasional Terhadap Laba Bersih - Widyastuti, Indria; Maharani, Maharani; Haryadi, Eko; Wijayanti, Diah (Cv. Syntax Corporation Indonesia, 2024)
In the business world, effective and efficient cost management is the key to optimizing company profits. The aim of this research is to examine the effect of production and operational expenditure on profit levels at PT Bakrie Metal Industries. The sample in this research refers to the production planning budget report. The method used is a descriptive quantitative research approach, with data obtained through the process of collecting information from production budget planning reports from 2020 to 2022 at PT. Bakrie Metal Industries, a company specializing in the production of corrugated metal products and fabrication projects. The research subject involves production costs, operational costs and net profit from the period 2020 to 2022. Data analysis was carried out through a number of techniques, including normality tests, heteroscedasticity tests, multicollinearity, autocorrelation test, correlation test, multiple linear regression test, coefficient of determination test, as well as t test and F test. The analysis process uses SPSS version 22 software. The results of this research indicate that production costs have an insignificant influence on net profit, while operational costs show a significant influence on net profit. Furthermore, it was found that both production costs and operational costs had a significant impact on the level of profitability at PT Bakrie Metal Industries.